Arnett Facial Soft-tissue Cephalometric Analysis Norms for Mongolian Children - Purevjav, Erdenebulgan; Ganburged, Ganjargal; Bazar, Amarsaikhan; Mukhtar, Yerkyebulan; Moriyama, Keiji (Central Asian Journal of Medical Sciences, 2020)
Objectives: This study aimed to determine norms cephalometric norms of Mongolian children and compare their development in boys and girls between 6 and 15 years of age. Methods: Lateral cephalograms were performed on 541 subjects (225 male and 316 females) having normal occlusion between the ages of 6 to 15 years.All radiographs were digitized on a computer using a cephalometric software program. A total of 6 angular, 38 linear measurements were measured by a radiologist for skeletal hard and soft tissue analysis. Results: Mx-ocdusal plane angle, Md1 to Md occlusal plane angle. Nasolabial angle decreased with age. Mx1, Mx occlusal plane angle, and overbite were stable with age. In contrast, the other measurements typically increased with age. No statistically significant gender differences were observed. Some distinct ethnic differences were found between Caucasians and Mongolian children with Mongolian children having thinner and shorter lips compared to Caucasians. Conclusions: No significant differences were observed in any of the dentoskeletal factors representing hard tissue to hard tissue measurements. Results were similar to those found in Caucasian males and females.